Analisis Model Pembelajaran Sesuai dengan Gaya Belajar Anak Sekolah Dasar yang Beragam - Ubaidillah, Muhammad Farid; Yusuf, Arba’iyah; Mubaroq, Muhammad Abror; Jauhari, Muhammad Adam (ALSYS, 2023)
One of the problems of education in Indonesia is the phenomenon of low learning outcomes of elementary school (SD) age children. The low learning outcomes occur because educators often cannot understand how the right aspects of learning to be applied to elementary school-age children, so understanding is needed for educators to formulate learning models that suit the various teaching styles of elementary school students. This study uses a systematic literature review method, analyzing related articles and formulating them into discussions about problem formulations, learning models that match the diverse visual, auditorial and kinesthetic learning styles of elementary school students. The results of this study formulate a learning model that suits the learning style of elementary school students that has a positive impact in the form of improving learning outcomes, namely: 1) Problem Based Learning based learning model for visual learning styles, 2) Discovery Learning-based learning model for auditorial and visual learning styles, 3) PAKEM learning model for kinesthetic learning styles, 4) Inquiry learning model for visual, auditorial and kinesthetic learning styles, 5) Student Team Achievement Division (STAD) cooperative-based learning model for auditorial and visual learning styles. This research can be implemented by teachers to elementary school students as a form of effort to improve the quality of student learning and as an effort to advance education in Indonesia.